2011
DOI: 10.1093/jac/dkr349
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of extraintestinal pathogenic Escherichia coli isolates from a regional cohort of elderly patients highlights the prevalence of ST131 strains with increased antimicrobial resistance in both community and hospital care settings

Abstract: The level of antibiotic resistance or virulence gene possession in uropathogenic E. coli is not directly associated with the healthcare setting of the patient, but there is a variation in antibiotic resistance and virulence gene possession depending on clonal group. ST131 is highly virulent and demonstrates high levels of antibiotic resistance, but its virulence does not appear to be attributable to the possession of a specific virulence-associated gene set or the possession of any virulence-associated gene in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
69
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 22 publications
6
69
1
1
Order By: Relevance
“…CC131 (22% of the isolates), ST73 (11% of the isolates), and ST69 (9% of the isolates) were identified as the most highly represented clones in this collection. Interestingly, only 3% of the urine isolates belonged to ST95 (43). A very similar picture regarding the most prevalent phylogenetic lineages can be painted for the strain collection used in this study.…”
Section: Discussionsupporting
confidence: 60%
“…CC131 (22% of the isolates), ST73 (11% of the isolates), and ST69 (9% of the isolates) were identified as the most highly represented clones in this collection. Interestingly, only 3% of the urine isolates belonged to ST95 (43). A very similar picture regarding the most prevalent phylogenetic lineages can be painted for the strain collection used in this study.…”
Section: Discussionsupporting
confidence: 60%
“…ST131 was initially considered to be particularly prevalent in community settings (1), but subsequent findings suggested otherwise (31). Here, ST131 was significantly associated with community acquisition, which accounted for 40/44 (91%) of ST131 isolates versus 53/71 (75%) of non-ST131 isolates (P Ͻ 0.001).…”
Section: Discussionmentioning
confidence: 77%
“…Le Gall et al identified nine subgroups within group B2. Clermont et al placed E. coli ST131 in subgroup I, which was suggested to be the basal subgroup of B2 strains (15), suggesting that the characteristics of non-ST131 B2 strains may have evolved after the divergence of ST131 and related genotypes (ST1680, ST1982, and ST1461), (16,17). E. coli ST131 strains are mostly of serotype O25:H4, with a specific O25 type, O25b.…”
Section: Bacterial Characteristicsmentioning
confidence: 99%